Evolving Strategies in India$1 (Bs Technological Self-reliance : s Patent Policies, R&D Incentives, and Human Resource Development - Sunil Mani
India$1 (Bs drive for technological self-reliance has shaped its development since the five-year plans began. This paper examines the evolution of this agenda through three key policy areas: patent policy, R&D tax incentives, and human resource development in science and technology. Early efforts focused on building domestic capabilities in sectors like agriculture, defence, and space by establishing public research institutions, encouraging corporate R&D, and creating public enterprises. Initially supported by regulated foreign technology transfers, India$1 (Bs approach has since evolved, reflecting changing global and domestic innovation dynamics.s
Keywords: ECO; India; Technological Self-reliance; Patent Policies; Research and development; Human Resource Development; Public research institutions; Innovation dynamics